Factors Influencing An Auditor's Ability To Detect Fraud: The Role Of Auditor Experience As A Moderating Variable (Empirical Study Of Public Accounting Firms In South Jakarta) - Yuwono, Bayu Tri; Sarwoko, Haris (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
The ability of auditors to detect fraud is an intriguing topic to explore, considering that evidence in the field shows many companies still manipulate financial statements to present misleading depictions of their performance. This issue poses a significant challenge in supporting the vision of "Indonesia Emas 2045" without cases such as asset misappropriation, financial statement fraud, and corruption. This study aims to identify the factors influencing auditors' ability to detect fraud in public accounting firms (KAP) in South Jakarta. Using a quantitative research approach, the population of this study consisted of public accounting firms in South Jakarta listed in the 2024 directory, totaling 10 KAPs. The sampling technique employed was non-probability sampling with the convenience sampling method, resulting in a sample of 95 auditors. Data analysis was conducted using outer model analysis, inner model analysis, and hypothesis testing with the assistance of SMART-PLS software. The findings of this study indicate that independence, professional skepticism, competence, and time pressure significantly influence auditors' ability to detect fraud. Additionally, auditor experience strengthens the relationships between independence, professional skepticism, and competence with the ability to detect fraud. However, auditor experience does not enhance the effect of time pressure on fraud detection.